Clinical efficacy and safety of T-DM1 for patients with HER2-positive breast cancer - Ma, Bo (Onco Targets Ther, 2016)
PURPOSE: The aim of this study was to evaluate the therapeutic efficacy and safety of trastuzumab emtansine (T-DM1) for the treatment of patients with human epidermal growth factor receptor 2-positive breast cancer. METHODS: We performed a systemic review and meta-analysis of the relevant published clinical studies. A computerized search was performed for controlled clinical trials of T-DM1 in targeted treatment. Overall survival, progression-free survival, objective response rate, symptom progression free, and adverse events (AEs) were evaluated. RESULTS: Eight eligible trials with a total of 2,016 patients with breast cancer were included in the present meta-analysis. The treatment of patients with breast cancer with T-DM1 was associated with significantly increased overall and progression-free survival when compared with controls (P<0.0001). An analysis of the objective response rate and symptom progression free also demonstrated favorable results for T-DM1 treatment (P≤0.0001). There was no significant difference between the T-DM1 and control groups with respect to nonhematologic or hematologic AEs (P=0.99 and P=0.30, respectively). CONCLUSION: Overall, T-DM1 is efficacious in the treatment of patients with human epidermal growth factor receptor 2-positive breast cancer and low rates of AEs compared with controls.